2022
DOI: 10.4149/bll_2022_092
|View full text |Cite
|
Sign up to set email alerts
|

Hyperleptinemia as a risk factor for post-transplant diabetes mellitus development after kidney transplantation

Abstract: INTRODUCTION: Adipose tissue is involved in the synthesis of hormones that have an impact on food intake regulation, control of insulin sensitivity or regulation of infl ammatory processes. The aim of this study was to determine the importance of adipocytokines and interleukins levels for the development of post-transplant diabetes mellitus (PTDM) after kidney transplantation (KT). MATERIAL AND METHODS: In the prospective analysis, the studied sample (n = 104) was divided into the control group, prediabetes gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Monitoring adipose tissue hormones in association with cardiometabolic risk factors has only a short history in the transplant population, and until now these hormones have been used as separate variables. In previous studies, we confirmed that hyperleptinemia is an independent risk factor for the development of PTDM, and a low level of adiponectin was associated with insulin resistance and obesity [15].…”
Section: Discussionsupporting
confidence: 82%
“…Monitoring adipose tissue hormones in association with cardiometabolic risk factors has only a short history in the transplant population, and until now these hormones have been used as separate variables. In previous studies, we confirmed that hyperleptinemia is an independent risk factor for the development of PTDM, and a low level of adiponectin was associated with insulin resistance and obesity [15].…”
Section: Discussionsupporting
confidence: 82%